2012
DOI: 10.1177/1477370812440065
|View full text |Cite
|
Sign up to set email alerts
|

Does the mobility of foreign offenders fit the general pattern of mobility?

Abstract: Research on offender mobility is directed to three main elements: distance, anchor points, and direction. Previous research in geographic criminology revealed that: (1) the journey to crime is limited in distance and follows a distance decay pattern; (2) the home of the offender plays a central role as the starting point of crime trips; and (3) the direction of their trip influenced by the opportunities to commit their crimes. The findings are more or less accepted as 'laws' in the field. However, research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Although studies on homicide have not addressed this relationship, the study by Van Daele et al. (2012) found that in foreign criminals, the perception of what is far away may be distorted, with no mental barrier of being on a long journey, leading them to travel a greater distance without being aware of it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies on homicide have not addressed this relationship, the study by Van Daele et al. (2012) found that in foreign criminals, the perception of what is far away may be distorted, with no mental barrier of being on a long journey, leading them to travel a greater distance without being aware of it.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focus on the potential differences between national and foreign offenders, which have been found to be associated with different types of homicide (e.g., Vatnar, Friestad, & Bjorkly, 2019). Regarding the possible influence of the country of origin on movement, the study by Van Daele, Vander Beken, and Bruinsma (2012) found that foreign criminals travelled twice as far than nationals. It is worth noting that many of these foreign offenders did not perceive the journey made as being particularly long, reflecting the fact that perceptions of the distance travelled are something that vary between individuals, and in the case of foreigners, it may be influenced by a less developed mind map that gives them a somewhat distorted perception of the near–far distance dichotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not the relationship between geographical dispersion and arrest rate is linked to the organization of police investigations, our findings may have consequences for the interpretation of the results of studies on offender mobility. Most importantly, because less geographically dispersed offenders have a greater probability of being arrested and thus a greater probability of being present in official police data, studies based on official arrest data might underestimate the geographical range of offenders, and might therefore also underestimate the distance that offenders travel between their homes and the locations of the crimes they perpetrate (see also Van Daele et al, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies on foreign nationals are often characterised by deficit-based and problem-oriented discourses, for instance, by focusing on their crime trips (Van Daele et al, 2012) or pains of imprisonment (Ugelvik and Damsa, 2018;Warr, 2016).…”
Section: Data Collection and Analysismentioning
confidence: 99%